Gut microbiota dysbiosis and protein energy wasting in patients on hemodialysis: an observational longitudinal study - Bi, Xiao; Liu, Yuqing; Yao, Lu; Ling, Lilu; Lu, Jianxin; Hu, Chun; Ding, Wei (Frontiers in Nutrition, 2024)
Background Protein energy wasting (PEW) is common in patients on hemodialysis, and its development may involve gut microbial dysbiosis. However, the exact relationship between the composition of different flora and the development of PEW remains unclear. Methods This is an observational longitudinal study on 115 patients undergoing hemodialysis who were followed up for 1 year. All the patients were evaluated at baseline, and different microbiota compositions were determined. After a 1 year follow-up period, the correlations between clinical parameter variations and the relative abundance of different gut flora were assessed using Spearman correlation. Moreover, the associations of the abundance of different gut microbiota with decrease in lean tissue mass and the development of PEW were analyzed using ROC curve and logistical regression analyses. Results We found that the relative abundances of Actinobacteria and Bifidobacteriaceae were significantly lower in patients with PEW than in those who did not develop PEW (p < 0.05). The abundance of Actinobacteria and Bifidobacteriaceae correlated positively with variations in serum albumin levels (r = 0.213, p = 0.035 and r = 0.214, p = 0.034, respectively), lean tissue mass (r = 0.296, p = 0.007 and r = 0.238, p = 0.002, respectively), and lean tissue index (r = 0.377, p < 0.001 and r = 0.419, p < 0.001, respectively). The area under the ROC curve or AUC values of Actinobacteria and Bifidobacteriaceae for the prediction of lean tissue mass decrease ranged from 0.676 to 0.708 (p < 0.05). Thus, decrease in the abundance of Actinobacteria and Bifidobacteriaceae may be associated with decrease in lean tissue mass and the occurrence of PEW. Conclusion The present findings imply Actinobacteria and Bifidobacteriaceae may be potential markers for predicting skeletal muscle mass decrease and PEW development in patients on hemodialysis.